SOSIALISASI PEMANFAATAN TEKNOLOGI DIGITAL BERBASIS WEBSITE UNTUK MENUNJANG KEGIATAN UMKM DI DESA MARGO LESTARI, KECAMATAN JATI AGUNG, KABUPATEN LAMPUNG SELATAN - Suhardi Suhardi; Riko Herdiansah; Lusia Komala Widiastuti (Jurnal Media Pengabdian Kepada Masyarakat, 2022)
Technological progress is unavoidable at this time, but not all people are able to optimize the existence of digital technology due to limited access and to qualified knowledge of technological developments. This condition has an impact on MSME owners who admit that it is difficult to expand their market reach. The purpose of community service activities is to provide solutions to problems faced by MSME owners through socializing the use of website-based digital technology to support MSME activities. The implementation of socialization activities is carried out using lecture methods, discussions, and directions related to websites with previously created domains. Based on data from observations made, it is known that 20 owners of MSME in Margo Lestari Village, Jati Agung District, South Lampung Regency have never used a website. The response of the participants in the socialization was generally good and positive, this can be seen based on the high enthusiasm of the participants to ask questions during the discussion session and fill in data to register their MSMEs on the website, so it is hoped that with this outreach activity, MSME owners can expand their market reach especially to the city of Bandar Lampung. Keywords: UMKM, Digital technology, Website